IDENTITY FORMATION OF MILLENNIAL GENERATION PARENTS TOWARDS THE TRADITION OF TEDHAK SITEN: Pembentukan Jati Diri Orang Tua Generasi Milenial Terhadap Tradisi Tedhak Siten - Muhammad Ikhsan fanani (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study examines the process of identity formation among millennial parents concerning the Tedhak Siten tradition in the modern era. Using qualitative methods through in-depth interviews with two pairs of millennial parents (Javanese-Madurese and Javanese-Javanese), this research aims to understand how the millennial generation interprets, experiences, and preserves the Tedhak Siten tradition. The findings indicate that despite the challenges of modernity and globalization, millennial parents still value the traditional values of Tedhak Siten and strive to preserve them through creative adaptations. Their identity formation process is characterized by negotiations between cultural heritage and the demands of modern life, resulting in a more flexible approach to the implementation of this tradition. The personal stories collected reveal how Tedhak Siten becomes an important moment in strengthening family bonds and instilling cultural values in children from an early age, despite various challenges such as time and financial constraints. Efforts to preserve this tradition through social media and informal education demonstrate that millennial parents are capable of balancing the preservation of cultural heritage with adaptation to modern life